Naltrexone‐bupropion (Mysimba®) in management of obesity: A systematic review and meta‐analysis of unpublished clinical study reports - Onakpoya, IJ; Lee, JJ; Mahtani, KR; Aronson, JK; Heneghan, CJ (Wiley, 2020)
Aims: To compare the benefits and harms of naltrexone–bupropion using evidence from clinical study reports.